Pengembangan Pembelajaran IPS Dalam Pembentukan Karakter Di SMP 2 Pungging Kabupaten Mojokerto - Noeryaningsih Pudjowati (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The Social Sciences Learning Model in Character Formation is a learning approach that allows students both individually and in groups to actively seek, explore and discover concepts and principles holistically and authentically and allows students to uphold morality, truth, goodness, strength and attitudes. someone who is shown to others through actions. This research aims to find out how social studies learning is implemented in developing characteristics in students at SMP 2 Pungging, Mojokerto Regency. The research method uses a qualitative descriptive approach to describe the role of social studies in the formation of student character at SMP 2 Pungging School, Mojokerto district. Data analysis uses Miles & Huberman which consists of Data Collection, Data Reduction, Data Display (Data Presentation), Drawing Conclusions. Findings (1) Social studies learning at SMP 2 Pungging, Mojokerto Regency provides opportunities for students to understand and apply social values ​​such as honesty, tolerance, cooperation, responsibility and justice (2) Social studies learning also focuses on students' understanding of their rights and obligations as citizens (3) Social studies learning also involves teaching about cultural, religious and ethnic diversity.